GENETIC DIVERSITY OF RHODIOLA sp. IN ALTAI AS ASSESSED BY INTRON POLYMORPHISM MARKERS - Tagimanova , D.; Khapilina , O.; Amenov , A.; Danilova , A.; Kalendar , R. (Eurasian Journal of Applied Biotechnology, 2017)
Roseroot (Rhodiola rosea L.) is a widely used medicinal herb in Russia, Scandinavia, and China. We used intron polymorphism markers for several genes families with high levels of polymorphism to investigate 32 accessions. In addition, we collected plants from 2 separate natural populations in the Altai region (West Altai and South Altai) of Kazakhstan. Universal PCR primer pairs were based on sequenced genes of related Rhodiolaspecies. The intron polymorphism markers were used to assess genetic diversityusing the GenAlex 6.5 program. The discriminatory potential of the selected markers was sufficientto determine the intrapopulation variability of Rhodiola. Observed heterozygosity at the loci averaged 0.235, compared to the expected 0.249. A dendrogram based on genetic distances was calculated from the results and confirmed that the two populations were genetically diverse. An analysis of molecular variance indicated that species level genetic diversity was relatively high (p = 70%) and an analysis using Shannon’s index showed that within and between genetic diversity in roseroot wasapproximately equal. Nei’s genetic distance and unweighted pair-group method with arithmetic averages cluster analysis showed that the two populations formed three major clusters. Understanding the genetic structure of R.rosea L. will improve the conservation and management of this endangered species.